SARS-CoV-2 vaccination in androgen sensitive phenotypes – A study on associated factors for SARS-CoV-2 vaccination and its adverse effects among androgenetic alopecia and benign prostate hyperplasia patients - Fan, Zhihua; Duan, Shixin; Liu, Fangfen; Shi, Wei; Yang, Ziye; Bai, Ruiyang; Li, Tao; Chen, Jingxian; Xie, Hongfu; Li, Ji; Tang, Yan (Frontiers in Immunology, 2022)
Background Androgen sensitivity, which was established as the leading etiology of androgenetic alopecia (AGA) and benign prostatic hyperplasia (BPH), plays an important role in SARS-CoV-2 infection. Vaccination is essential for AGA and BPH patients in view of the high risk from SARS-CoV-2 infection. Purpose We aimed to investigate the associated factors for SARS-CoV-2 vaccination and its side effects in populations with AGA and BPH. Method We collected the data on SARS-CoV-2 vaccination and adverse reactions of male AGA and BPH patients visited the outpatient of Xiangya hospital by telephone and web-based questionnaires. Vaccination rate and adverse reactions were compared by different vaccine types and use of anti-androgen therapy. Result A total of 457 AGA patients and 397 BPH patients were recruited in this study. Among which, 92.8% AGA patients and 61.0% BPH patients had at least the first dose of SARS-CoV-2 vaccination (p < 0.001). Having comorbidities and use of anti-androgen therapy increased the risk of un-vaccination among AGA by 2.875 and 3.729 times, respectively (p < 0.001). Around 31.1% AGA patients and 9.5% BPH patients presented adverse reactions, which were mostly mild. Anti-androgen therapy increased the inclination of injection site pain after vaccination (18.7% vs 11.9%; OR: 1.708, 95% CI: 1.088-2.683, p = 0.019). Conclusion Co-existence of other systemic diseases and anti-androgen therapy were the limiting factors for SARS-CoV-2 unvaccination, especially in AGA patients. The importance of SARS-CoV-2 vaccines should be strengthened and popularized in androgen sensitive phenotypes.